Navigating Educational Management in the Era of Digital Transformation - Muhammad Ihsan Dacholfany; Matnur Ritonga; Hiljati Hiljati; Loso Judijanto; Syamsuri Syamsuri (STAI Hubbulwathan Duri, 2024)
This study delved into the adaptation of educational management models in response to the challenges and opportunities presented by digital transformation within learning contexts. Employing a literature review methodology spanning from 2015 to 2023, the research conducted a comprehensive exploration and analysis of relevant studies, scholarly articles, and literature in the field of education and technology. Utilizing techniques of analysis and synthesis, insights extracted from the literature were systematically mapped and synthesized. The research outcomes identified patterns, perspectives, and pertinent strategies for aligning educational management models with the demands of digital transformation in learning environments. The analysis involved a thorough examination of primary data sources including academic journals, textbooks, and publications, providing a nuanced understanding of the evolving landscape of educational management amidst digital disruption. The synthesis process facilitated the integration of diverse perspectives and approaches, shedding light on effective strategies and best practices for adaptation. The results revealed a paradigm shift in educational management paradigms towards embracing technological integration, along with the emergence of innovative strategies to address implementation challenges. Visionary leadership, stakeholder engagement, strategic planning, and robust infrastructure were identified as key components in navigating digital transformation effectively within educational settings. In conclusion, the study underscores the imperative for educational institutions to proactively adapt their management models to leverage the opportunities presented by digital transformation. The findings have significant implications for policymakers, educators, and administrators, highlighting the need for strategic investments in leadership development, infrastructure, and professional development to facilitate seamless integration of digital technologies in learning environments.